2017
DOI: 10.1042/bsr20170144
|View full text |Cite|
|
Sign up to set email alerts
|

Role of SDF-1α/CXCR4 signaling pathway in clinicopathological features and prognosis of patients with nasopharyngeal carcinoma

Abstract: The present study aims to explore the role of stromal cell-derived factor-1α (SDF-1α)/stromal cell-derived factor receptor-4 (CXCR4) signaling pathway to the clinicopathological features and prognosis of patients with nasopharyngeal carcinoma (NPC). From January 2009 to December 2010, 102 patients with NPC and 80 patients with chronic nasopharyngitis were enrolled for the study. Immunohistochemical staining, quantitative real-time polymerase chain reaction (qRT-PCR), and Western blotting were employed to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The functional analysis supported that miR-9 could suppress the progression of NPC by targeting CXCR4, which is a key metastatic promoter and associated with the clinicopathological features and prognosis. 72 , 73 …”
Section: The Suppressive Roles Of Mir-9 In Metastasis Of Nasopharyngeal Carcinoma (Npc) Gastric Cancer (Gc) and Brain Cancermentioning
confidence: 99%
“…The functional analysis supported that miR-9 could suppress the progression of NPC by targeting CXCR4, which is a key metastatic promoter and associated with the clinicopathological features and prognosis. 72 , 73 …”
Section: The Suppressive Roles Of Mir-9 In Metastasis Of Nasopharyngeal Carcinoma (Npc) Gastric Cancer (Gc) and Brain Cancermentioning
confidence: 99%
“…Initial studies have suggested that CXCR4 + NPC cells have a stronger capability for invasion and metastasis [13][14][15]. CXCR4 may not be the only marker, but it remains the most widely reported marker of MCSCs in many types of cancer [11,12,16].…”
Section: Introductionmentioning
confidence: 99%